2021
DOI: 10.4103/jcar.jcar_14_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of cancer stem cells in head-and-neck squamous cell carcinoma – A systematic review

Abstract: Targeting cancer stem cell (CSC) subpopulation within the tumor remains an obstacle for specific therapy in head-and-neck squamous cell carcinoma (HNSCC). Few studies in the literature describe a panel of stem cell makers, however a distinct panel has not been put forth. This systematic review aims to enhance the knowledge of additional markers to accurately relate their expression to tumorigenesis, metastasis, and therapy resistance. Databases, including PubMed, Google Scholar, Ebsco, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…How that loss of homeostasis from chronic inflammation promotes progression to HNSCC remains largely unknown. The current studies demonstrate that MUC1-C drives STAT1-dependent chronic inflammation in HPV-negative HNSCC cells and thereby induction of the ∆Np63 ( 9, 30–32 ) and SOX2 ( 10, 33 ) TFs that have been linked to HNSCC pathogenesis. We also demonstrate that (i) MUC1-C signaling regulates the NOTCH3 pathway that contributes to the HNSCC CSC state ( 34, 35 ), and (ii) HNSCC cells are dependent on MUC1-C for self-renewal and tumorigenicity.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…How that loss of homeostasis from chronic inflammation promotes progression to HNSCC remains largely unknown. The current studies demonstrate that MUC1-C drives STAT1-dependent chronic inflammation in HPV-negative HNSCC cells and thereby induction of the ∆Np63 ( 9, 30–32 ) and SOX2 ( 10, 33 ) TFs that have been linked to HNSCC pathogenesis. We also demonstrate that (i) MUC1-C signaling regulates the NOTCH3 pathway that contributes to the HNSCC CSC state ( 34, 35 ), and (ii) HNSCC cells are dependent on MUC1-C for self-renewal and tumorigenicity.…”
Section: Introductionmentioning
confidence: 61%
“…SOX2 is essential for self-renewal of basal cells, which are the proposed origin of SCCs ( 30, 59 ). In addition, SOX2 contributes to progression of the SCC CSC state ( 10, 33 ). As found for ∆Np63, targeting MUC1-C in CAL27 and HSC3 cells downregulated SOX2 gene transcription and mRNA levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…reported that the three markers CD44, CD133, and ALDH were the most commonly expressed CSC markers in head and neck squamous cell carcinoma. 15 …”
Section: Resultsmentioning
confidence: 99%
“…(55) The major impediment to HNSCC is the presence of cancer stem cells, which have self-renewal abilities, high proliferation capacity, high migration capacity, drug resistance, resistance to chemo-and radiotherapies, and differentiation capacity. (56) These cells do not have specifi c cell markers known that can be used to identify and specifi cally target these cells, making it diffi cult to completely dry out the HNSCC, prolonging the time of coexistence with the disease. (56) Unlike GBC, HNSCC is easy to identify, however, there is still a long delay for its diagnosis, which ends up being done already in advanced stages, due to the low presentation of symptoms.…”
Section: Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…(56) These cells do not have specifi c cell markers known that can be used to identify and specifi cally target these cells, making it diffi cult to completely dry out the HNSCC, prolonging the time of coexistence with the disease. (56) Unlike GBC, HNSCC is easy to identify, however, there is still a long delay for its diagnosis, which ends up being done already in advanced stages, due to the low presentation of symptoms. (57) This delay in diagnosis and the prolongation of the time of living with the HNSCC translates into high expenses with medication and treatments for the various health systems, in addition to an increase in the queues for treatment.…”
Section: Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%